1997
DOI: 10.1007/s003810050096
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of 99m Tc-ECD and 99m Tc-HMPAO distributions in herpes simplex encephalitis

Abstract: In herpes simplex encephalitis (HSE), the authors noted an evident dissociation between the 99mTc-ethyl cysteinate dimer (ECD) and 99mTc-d,l-hexamethyl-propylene-amine oxime (HMPAO) single photon emission computed tomographies (SPECTs). The patient was a 5-year-old boy with diffuse type of pontine glioma, which was treated with hyperfractionated radiotherapy. Two weeks after the completion of radiation therapy, a lesion suggesting that of HSE was noted in the right fronto-temporal region on magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
1
9
0
2
Order By: Relevance
“…We conducted a review of the literature and found 14 previously reported cases of HSE in patients with gliomas,6–16 with details reported in online supplementary table S2. Consistently with that found in our series, HSE occurred during different steps of cancer history (in five patients perioperatively,7–9 in six patients during radiotherapy10–14 and in the last three patients within 3 months of its completion6 15 16), and evolution was characterised by high mortality or severe morbidity despite antiviral treatment.…”
Section: Discussionsupporting
confidence: 91%
“…We conducted a review of the literature and found 14 previously reported cases of HSE in patients with gliomas,6–16 with details reported in online supplementary table S2. Consistently with that found in our series, HSE occurred during different steps of cancer history (in five patients perioperatively,7–9 in six patients during radiotherapy10–14 and in the last three patients within 3 months of its completion6 15 16), and evolution was characterised by high mortality or severe morbidity despite antiviral treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Short-term follow-up evaluation showed aphasia and motor deficits (19). Another patient responded well to acyclovir but developed aphasia and mild hemiparesis (22). The outcome was not reported for the third patient (17).…”
Section: Discussionmentioning
confidence: 96%
“…Clinical presentation can be atypical in these cases with absent or mild pleocitosis in cerebrospinal fluid and initial negative findings on neuroimaging (17,19,22). In the few reported cases of HSE in patients with brain tumors, severe complications were fre-quent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have described cases of HSE that occurred after radiotherapy for CNS malignancies, as summarized in Table 1 [8][9][10][11][12][13][14]. In addition to these reports, HSE has been reproducibly observed in other case series of malignant glioma (2/81), medulloblastoma and primitive neuroectodermal tumor (1/14), and primary CNS lymphoma (1/14) receiving chemoradiotherapy [15][16][17].…”
Section: Case Reportmentioning
confidence: 94%